Use of Hydrant Pumps As A Strategy to Increase Rice Production Capacity in Mekarmulya Village, Karawang - Ade Suhara (Pengabdian: Jurnal Abdimas, 2025)
Background. The impact of poor land irrigation will result in serious problems for plants and harvest yields. Purpose. The aim of this community service activity is to overcome the problem of irrigation of land that is geographically located above the river surface through appropriate technology in the form of a hydraulic pump. Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. The results of this community service activity show that the hydraulic ram pump is an appropriate solution to the irrigation problems experienced by landowners in the highlands in the Karanglingar village area. Conclusion. By using this hydraulic pump, farmers and landowners are expected to be able to optimize land irrigation in the highland areas.